Cell-type specific binocular interactions in mouse visual thalamus - Sean P. Masterson; Govin Govindaiah; William Guido; Martha E. Bickford (iScience)
Summary: To determine whether intrinsic circuits of the dorsal lateral geniculate nucleus (dLGN) mediate excitatory and/or inhibitory binocular interactions, in vitro dual color optogenetics was used to examine convergence of eye-specific retinal inputs to thalamocortical (relay) cells and GABAergic interneurons. Both relay cells and interneurons were found to receive direct binocular retinogeniculate input, but the incidence was higher for interneurons. Moreover, the distribution of binocular relay cells was limited to regions in and around the ipsilateral patch of retinogeniculate terminals, while binocular interneurons were distributed throughout the dLGN. Accordingly, retinogeniculate-evoked inhibitory interactions were common. Retinal inputs arising from either eye inhibited the majority of relay cells via the activation of intrinsic interneuron circuits. In addition, the majority of interneurons were found to be interconnected, receiving both monocular and binocular retinogeniculate-evoked inhibition. These results reveal that intrinsic interneurons provide the primary source of binocular interactions within the dLGN.